The asthma-chronic obstructive pulmonary disease overlap syndrome: pharmacotherapeutic considerations - Louie, Samuel; Zeki, Amir A; Schivo, Michael; Chan, Andrew L; Yoneda, Ken Y; Avdalovic, Mark; Morrissey, Brian M; Albertson, Timothy E (Expert review of clinical pharmacology, 2013)
Asthma-chronic obstructive pulmonary disease (COPD) overlap syndrome (ACOS) is a commonly encountered yet loosely defined clinical entity. ACOS accounts for approximately 15-25% of the obstructive airway diseases and patients experience worse outcomes compared with asthma or COPD alone. Patients with ACOS have the combined risk factors of smoking and atopy, are generally younger than patients with COPD and experience acute exacerbations with higher frequency and greater severity than lone COPD. Pharmacotherapeutic considerations require an integrated approach, first to identify the relevant clinical phenotype(s), then to determine the best available therapy. The authors discuss the array of existing and emerging classes of drugs that could benefit those with ACOS and share their therapeutic approach. A consensus international definition of ACOS is needed to design prospective, randomized clinical trials to evaluate specific drug interventions on important outcomes such as lung function, acute exacerbations, quality of life and mortality.